Evaluation of the neonatal sequential organ failure assessment and mortality risk in neonates with respiratory distress syndrome: A retrospective cohort study - Shi, Shanshan; Guo, Jie; Fu, Minqiang; Liao, Lihua; Tu, Jiabin; Xiong, Jialing; Liao, Quanwang; Chen, Weihua; Chen, Kaihong; Liao, Ying (Frontiers in Pediatrics, 2022)
Abstract Background: Respiratory distress syndrome (RDS) is one of the leading causes of neonatal death in the neonatal intensive care unit (NICU). Previous studies have suggested that the development of neonatal RDS may be associated with inflammation and lead to organ dysfunction. The neonatal sequential organ failure assessment (nSOFA) scoring system is an operational definition of organ dysfunction, but whether it can be used to predict mortality in neonates RDS is unknown. The aim of this study was to clarify the performance of the nSOFA score in predicting mortality in patients with neonatal RDS, with the aim of broadening the clinical application of the nSOFA score. Methods: Neonates with RDS were identified from the Medical Information Mart for Intensive Care (MIMIC)-III database. A cox proportional hazards model were used to assess the association between nSOFA score and mortality. Propensity score matched analysis were used to assess the robustness of the analytical results. Results: In this study of 1281 patients with RDS of which 57.2% were male, death occurred in 40 cases (3.1%). Patients with high nSOFA scores had a higher mortality rate of 10.7% compared with low nSOFA scores at 0.3%. After adjusting for confounding, multivariate cox proportional risk analysis showed that an increase in nSOFA score was significantly associated with increased mortality in patients with RDS [adjusted Hazards Ratio (aHR): 1.48, 95% Confidence Interval (CI): 1.32-1.67; P < 0.001]. Similarly, the High nSOFA group was significantly associated with higher mortality in RDS patients (aHR: 19.35, 95% CI: 4.41-84.95; P < 0.001) compared with the low nSOFA group. Conclusion: The nSOFA score was positively associated with the risk of mortality in cases of neonatal RDS in the NICU, where its use may help clinicians to quickly and accurately identify high risk neonates and implement more aggressive intervention.